English for Academic Purposes: E-Module of Writing a Report for Food Processing Technology Students - Areta Puspa; Mohammad Adnan Latief; Emalia Iragiliati (Pascasarjana Universitas Negeri Malang, 2018)
This study is aimed to produce E-module of writing a report for students of Food Processing Technology study program who join apprenticeship program. This study was a research and development method that was adapted from Borg and Gall (1996), and Latief (2014), to be precise (1) investigation of problem identification, (2) developing materials, (3) experts validation, (4) product try out, and (5) final product. The result of development was four units that were (1) Aspects of writing, (2) Planning, (3) Drafting, (4) Revising and Editing employing Writing Process Approach. The product was as the supplementary materials in the form of PDF File that used deductive learning in each unit providing explanation, examples (models), and practices. This result of this study is benefit for the students' independent learning in writing their apprenticeship report. Recommendations for the future researcher are also discussed. Penelitian ini bertujuan untuk menghasilkan E-modul penulisan laporan untuk mahasiswa Program Studi Teknologi Pengolahan Pangan yang mengikuti program magang. Penelitian ini merupakan metode penelitian dan pengembangan yang diadaptasi dari Borg and Gall (1996) dan Latief (2014), tepatnya (1) investigasi identifikasi masalah, (2) pengembangan materi, (3) validasi ahli, (4) produk dicoba, dan (5) produk akhir. Hasil pengembangan adalah empat unit, yaitu (1) aspek penulisan, (2) perencanaan, (3) penyusunan, (4) revisi dan pengeditan yang menggunakan Pendekatan Proses Penulisan. Produk itu sebagai bahan pelengkap berupa PDF yang menggunakan pembelajaran deduktif di setiap unit yang memberikan penjelasan, contoh (model), dan praktik. Hasil penelitian ini bermanfaat bagi pembelajaran mandiri siswa dalam menulis laporan magang mereka. Rekomendasi untuk peneliti masa depan juga dibahas.